Analysis Of Catching Technique Skills In Ukm Cricket Athletes Of Jambi University - Putri, Dini Amelia; Ali, Muhammad; Putra, Anggrawan Januar (Jurnal Pendidikan Jasmani (JPJ), 2025)
This study aims to analyze the catching technique skills of athletes from the Jambi University Cricket Student Activity Unit (UKM). Catching technique is one of the fundamental aspects in cricket that greatly determines the success of the team, especially in preventing the opponent from scoring points. This study uses a quantitative descriptive method with a survey approach. The sample in this study were all members of the Jambi University Cricket UKM totaling 20 people (10 male and 10 female), who were selected using the total sampling technique. The instrument used was an observation sheet for catching technique skills, which included four stages of catching technique: basic, bouncing bottom ball, rolling bottom ball, and top ball. The results showed that 25% of athletes were in the "Very Good" category, 35% in the "Good" category, and 40% in the "Moderate" category. There were no athletes in the "Poor" or "Very Poor" categories. The average overall score was 71%, indicating that the athletes' catching technique skills were at a fairly good level, but there was still room for improvement, especially in the aspect of catching the upper ball which showed the lowest results. These findings provide recommendations for coaches to design more focused and specific training programs to improve the athletes' catching abilities.